Behavioural Intention to Use MYOB Accounting Application among Accounting Students - Fitri Puspa, Dwi; Ilona, Desi; Zaitul (Journal of physics. Conference series, 2019)
This research aims to investigate the effect of effort expectancy, performance expectation, facility condition and social influence on behavioural intention to use MYOB accounting application. The unified technology acceptance and use of technology (UTAUT) is used to underpin the relationship. University of Bung Hatta's accounting students registered at computer accounting subject in first session of academic year of 2018/2019 are research object. Seventy-seven students are participated in this study. Using the smart-pls, we found that there is a positive relationship between performance expectation and social influence with behavioural intention. Theoretically, this study partially contributes to the UTAUT. Practically, this finding can be used to increase the behavioural intention to use MYOB among accounting students by increase the performance expectation and social influence.